Intermolecular C–H Amidation of Alkenes with Carbon Monoxide and Azides via Tandem Palladium Catalysis - Gu, Zheng-Yang; Wu, Yang; Jin, Feng; Bao, Xiaoguang; Xia, Ji-Bao (Synthesis, 2021)
An atom- and step-economic intermolecular multi-component palladium-catalyzed C–H amidation of alkenes with carbon monoxide and organic azides has been developed for the synthesis of alkenyl amides. The reaction proceeds efficiently without an ortho-directing group on the alkene substrates. Nontoxic dinitrogen is generated as the sole by-product. Computational studies and control experiments have revealed that the reaction takes place via an unexpected mechanism by tandem palladium catalysis.
Keywords: C–H carbonylation; amidation; palladium; alkene; amides